The Effect of Edamame Decoction on Breast Milk Production in Breastfeeding Mothers from 2 Days to 1 Week with Insufficient Milk Flow in Kertonegoro Village, Jember - Fatmawati, Yuris; Keswara, Nila Widya (Jurnal EduHealth, 2025)
Breast milk (ASI) is strongly recommended as the sole intake for infants during the first six months of life. It serves as the primary and optimal source of nutrition for babies. Consuming additional nutritious foods is crucial during the breastfeeding period, as it can support breast milk production. Edamame has the potential to be a nutritional source that supports maternal health due to its phytosterol content, which contributes to additional nutrition and can help increase breast milk volume. This study aims to identify the contribution of edamame decoction in supporting breast milk production in breastfeeding mothers from the second day to the first week postpartum with insufficient milk flow in Kertonegoro Village, Jember. The research design used was a pre-experimental approach with a one-group pre-test and post-test design. The sample was selected using purposive sampling, involving 15 breastfeeding mothers between days 2 to 7 postpartum. The study was conducted over a two-week period and employed the Wilcoxon statistical test for analysis. The results showed a p-value of 0.001, indicating that there is a significant effect of edamame decoction on breast milk production in breastfeeding mothers on days 2–7 in Kertonegoro Village, Jember. Health workers are expected to provide education about adequate nutrition for postpartum mothers during the breastfeeding period, as it can support the achievement of government programs aimed at increasing the coverage of exclusive breastfeeding.